Moses the Egyptian in the illustrated Old English Hexateuch (London, British Library Cotton MS Claudius B.iv) - Broderick, Herbert Reginald (University of Notre Dame Press, 2017)
In Moses the Egyptian, Herbert Broderick analyzes the iconography of Moses in the famous illuminated eleventh-century manuscript known as the Illustrated Old English Hexateuch. A translation into Old English of the first six books of the Bible, the manuscript contains over 390 images, of which 127 depict Moses with a variety of distinctive visual attributes